Still Strugling with COVID-19 Pandemi - Irma Ruslina Defi (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
Since this issue on the COVID-19 pandemic started, the entire world is still in the middle of thecrisis, although less intensely so than during the earlier period of tremendous lockdown. We haveall been affected by the crisis in some way and have been forced to adapt. While it remains to beseen whether the markers of social experiences will become part of the “new normal,” one thing iscertain for intellectual work: researchers will need to record and analyze how different societies havebeen managed inability to respond to the COVID-19 problematics, to learn from one another and topinpoint the working logics of various social formations.